Qin Shi Huang's Legacy: Assessing the First Emperor's Impact on Chinese History - Abbas, Syed Tahir (PT FORMOSA CENDEKIA GLOBAL, 2024)
Qin Shi Huang, the first emperor of China, stands as a transformative figure in Chinese history, leaving a lasting impact that reverberates through millennia. This comprehensive exploration delves into the multifaceted dimensions of his rule, assessing his achievements, controversies, and enduring legacy. From his early life in the tumultuous Warring States period to the unification of China through ambitious military campaigns, Qin Shi Huang's journey unfolds against a backdrop of political intrigue and strategic brilliance. The examination of his governance reveals the imprint of Legalist philosophy, with centralization, administrative reforms, and standardized systems shaping the Qin Dynasty's brief but impactful existence. The study evaluates the cultural achievements that define Qin Shi Huang's legacy, notably the Terracotta Army and monumental constructions like the Great Wall. Beyond the archaeological marvels, the paper probes the controversies surrounding his rule, including harsh legal measures, the suppression of Confucianism, and the burning of books. Modern perspectives offer a nuanced reevaluation of his legacy in contemporary China, exploring the relevance of his governance structures and the cultural significance of his achievements in the 21st century. Qin Shi Huang's influence on subsequent dynasties, particularly the Han, is scrutinized, highlighting the enduring elements of his governance that shaped Chinese political thought. The abstract concludes by emphasizing the continued relevance of Qin Shi Huang's legacy, providing insights into the complexities of leadership, governance, and the continuity of Chinese history. As debates surrounding his legacy persist, Qin Shi Huang remains an enigmatic figure whose historical significance extends beyond his time, contributing to a dynamic discourse on China's past and its implications for the present and future